Efficacy of fluorescence diagnosis for pleural tumors with alasens - O. V. Pikin; E. V. Filonenko; D. E. Mironenko (Biomedical Photonics, 2013)
The study of efficacy of thoracoscopy-assisted fluorescence diagnosis with Alasens is described in the article. The results of fluorescence diagnosis in 27 patients with suspicion on pleral tumor are represented. Before thoracoscopy-assisted fluorescence diagnosis in 21 patients according to radiological studies there was a fluid in pleural ca, in 19 patients of them tumor cells were found by cytological study of pleural fluid, in 10 patients differential diagnosis was performed between mesothelioma and adenogenic cancer. For fluorescence diagnosis fluorescence system by company Кarl Storz and xenon lamp with set of light filters was used: fluorescence study was performed by excitation at wavelength 380–460 nm. 3 h before investigation the patient received alasens per os in dose of 30 mg/kg body weight in 100 ml of water. For routine thoracoscopy tumor lesions were determined in 20 (87.0%) patients, other 3 (13.0%) patients had no tumors. In the group of patients with tumor lesions determined by routine thoracoscopy the fluorescence during fluorescence study was registered in all lesions determined in white light, besides this 24 additional foci of fluorescence were noticed, according to morphological study 21 of them had tumor nature, 3 lesions were inflammatory. In 1 of 3 patients with no lesion in white light there was one focus of fluorescence, morphological study proved the metastasis of adenocarcinoma in this area. According to morphological study of pleural biopsy specimens the true-positive results for fluorescence thoracoscopy accounted for 82, false-negative – 10, true-negative – 23, false-positive – 3. The sensitivity of the method was 89,1%, the specificity – 88,4%, the diagnostic accuracy – 88,9%.